2012
DOI: 10.15395/mkb.v44n1.71
|View full text |Cite
|
Sign up to set email alerts
|

Toksisitas Akut per Oral Ekstrak Etanol Daun Dewa (Gynura pseudochina (Lour.) DC) terhadap Kondisi Lambung Tikus Jantan dan Betina Galur Wistar

Abstract: AbstrakToksisitas oral akut merupakan efek samping yang terjadi dalam waktu singkat melalui pemberian tunggal per oral ataupun dengan dosis berulang dalam waktu 24 jam dan dapat terjadi pada setiap organ tubuh. Traktus gastrointestinal sangat potensial terhadap paparan agen toksik yang tampak sebagai gambaran erosi dan tukak. Penelitian ini merupakan penelitian eksperimental uji toksisitas akut per oral dan dilakukan di laboratorium Farmakologi Klinik RS Dr. Hasan Sadikin Bandung pada bulan Juli-September 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…The results of previous study showed that administration of GD extract at a dose of 750 mg/kg/day for 14 days had a significant effect on the increase of SGOT levels and an insignificant effect on SGPT levels in the treatment group [13]. The results of a previous study conducted an oral acute toxicity test of the ethanol extract of Dewa leaves (Gynura Pseudochina L.) on the stomach conditions of male and female Wistar rats also shows that the content of flavonoids in GD at a dose of 1625 mg/kg/day given for 14 days has an inhibitory effect on lipoxygenase and cyclooxygenase which causes discontinuity in the gastric mucosal epithelium which can cause changes in the shape of the stomach organs [14].…”
Section: Resultsmentioning
confidence: 93%
“…The results of previous study showed that administration of GD extract at a dose of 750 mg/kg/day for 14 days had a significant effect on the increase of SGOT levels and an insignificant effect on SGPT levels in the treatment group [13]. The results of a previous study conducted an oral acute toxicity test of the ethanol extract of Dewa leaves (Gynura Pseudochina L.) on the stomach conditions of male and female Wistar rats also shows that the content of flavonoids in GD at a dose of 1625 mg/kg/day given for 14 days has an inhibitory effect on lipoxygenase and cyclooxygenase which causes discontinuity in the gastric mucosal epithelium which can cause changes in the shape of the stomach organs [14].…”
Section: Resultsmentioning
confidence: 93%
“…Apabila suatu kandidat obat terdeteksi toksisitas akut, maka dapat dipastikan obat tersebut tidak dapat dilanjutkan sebagai pertimbangan kandidat obat, karena dapat menganggu kesehatan manusia (Yang et al, 2018). Selain itu, dilakukan uji toksisitas oral akut bertujuan mengetahui dampak yang ditimbulkan pada pemberian obat tunggal dalam kurun waktu 24 jam (Astri et al, 2012). Berdasarkan tingkat toksisitas dari suatu bahan kimia yang dinyatakan dalam median lethal dosis (LD50) dan ditinjau berdasarkan kriteria oleh US Environmental Protection Agency (EPA), terdapat empat kategori: a) kategori I memiliki nilai ≤50 mg/kg tergolong sebagai sangat racun dan dapat berakibat fatal jika tertelan; b) kategori II memiliki nilai 50<x≤500 mg/kg tergolong sebagai cukup beracun; c) kategori III memiliki nilai 500<x≤5000 mg/kg tergolong sebagai sedikit beracun; dan d) kategori IV memiliki nilai >5000 mg/kg tergolong sebagai tidak beracun (Li et al, 2014).…”
Section: ) Sehingga 5-amino-2-[[6-(3-carbamoyl-4-cyanophenoxy)-2-[3-(...unclassified
“…A deficiency of prostaglandins is suspected to lead to a decrease in the production of mucus, phospholipids, HCO3secretions, the proliferation of mucosal cells, and microvascular flow of the stomach that is suspected to cause discontinuities in the epithelium of the gastric mucosa known as peptic ulcers. The mechanism is suspected to be the cause of swelling of the gastric organs in male white mice and female white mice after administration of the Kayu Manis cortex fraction (Astri et al, 2012).…”
Section: Organ Weight Ratiomentioning
confidence: 99%